2021
DOI: 10.3389/fpsyg.2021.655121
|View full text |Cite
|
Sign up to set email alerts
|

BeatWalk: Personalized Music-Based Gait Rehabilitation in Parkinson’s Disease

Abstract: Taking regular walks when living with Parkinson’s disease (PD) has beneficial effects on movement and quality of life. Yet, patients usually show reduced physical activity compared to healthy older adults. Using auditory stimulation such as music can facilitate walking but patients vary significantly in their response. An individualized approach adapting musical tempo to patients’ gait cadence, and capitalizing on these individual differences, is likely to provide a rewarding experience, increasing motivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 47 publications
0
67
0
Order By: Relevance
“…Recent evidence also suggests that RAS-assisted gait training significantly reduces patients’ overall fear of falling ( Thaut et al, 2019 ; Capato et al, 2020b ; Naro et al, 2020 ; Cochen De Cock et al, 2021 ) and the number of falls ( Thaut et al, 2019 ). Using a randomized withdrawal/discontinuation design, a recent study investigated the effect of RAS on incidences of falls in 47 participants with moderate to severe stages of PD (H&Y 3 and 4) with a history of falls ( Thaut et al, 2019 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence also suggests that RAS-assisted gait training significantly reduces patients’ overall fear of falling ( Thaut et al, 2019 ; Capato et al, 2020b ; Naro et al, 2020 ; Cochen De Cock et al, 2021 ) and the number of falls ( Thaut et al, 2019 ). Using a randomized withdrawal/discontinuation design, a recent study investigated the effect of RAS on incidences of falls in 47 participants with moderate to severe stages of PD (H&Y 3 and 4) with a history of falls ( Thaut et al, 2019 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Recent advances in mobile technologies whereby motor behaviors can be monitored via dedicated sensors may be instrumental to implementing assistive rehabilitation strategies via apps, serious games, or touchscreen musical instruments on tablets ( Dalla Bella, 2018 ). For instance, a recent open-label clinical trial demonstrated the beneficial effects of a 1-month (30 min/day, 5 days) gait training with auditory rhythm in a home setting with 45 patients with moderate PD via the use of a smartphone application combined with ankle-worn sensors ( Cochen De Cock et al, 2021 ). Street et al (2020) discussed the potential use of touchscreen devices (iPad) in acute stroke rehabilitation as tools to enhance treatment dosage and engagement.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Technologies, such as dedicated apps on smartphone and tablet devices, coupled with external sensors, 88,89 are recent additions to the methods for music-based interventions. 9 Implementing music-based interventions as serious games has several advantages, such as making them particularly motivating and rewarding, allowing performance monitoring and individualization, which all should add to the potential of music as a tool for rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…52 One study looked at the effects of Tango and Ballroom dancing classes on balance control and locomotion in PD patients, showing significant improvements in both. 53 Music-based gait rehabilitation 54 has also been studied as a means to incorporate the effect of rhythm into movement.…”
Section: Nonpharmacologic Treatments In Parkinson's Diseasementioning
confidence: 99%